Analisis Kuantitatif Flavonoid Total dalam Ekstrak Daun Bidara (Ziziphus mauritiana) sebagai Dasar Pengembangan Produk Farmasi Alami: Quantitative Analysis of Total Flavonoids in Bidara (Ziziphus mauritiana) Leaf Extract as a Basis for Natural Pharmaceutical Product Development - Christian, Yulius Evan; Chandra, Pra Panca Bayu; Hermawati, Ema; Ismyama, Dian Farida (Binawan Student Journal, 2025)
Bidara leaves (Ziziphus mauritiana) are a herbal plant that is known to be rich in bioactive compounds, especially flavonoids, which have antioxidant, anti-inflammatory and antimicrobial activities. This study aims to determine the total flavonoid content in bidara leaf extract and evaluate the potential of its secondary metabolites for pharmaceutical and cosmetic applications. Phytochemical screening was carried out to identify secondary metabolite content, which included flavonoids, alkaloids, saponins, tannins and phenolics. Extraction was carried out using the maceration method with 96% ethanol solvent, followed by filtering and evaporation of the solvent using a rotary vacuum evaporator at a temperature of 40°C to produce a thick extract. Determination of total flavonoid levels was carried out using the UV-Vis spectrophotometric method with aluminum chloride reagent at a wavelength of 441 nm, using quercetin as a standard. The results showed that the total flavonoid content in bidara leaf extract reached 3202.43 mg QE/100 g dry extract. This high flavonoid content supports antioxidant activity through the mechanism of capturing free radicals, chelating transition metal ions, and inhibiting lipid peroxidation. In addition, the flavonoids in the extract have the potential to be anti-inflammatory by inhibiting pro-inflammatory enzymes and modulating cytokines, as well as antimicrobial through disrupting microbial membranes. The conclusion of this research is that bidara leaf extract has great potential to be developed as an active ingredient in pharmaceutical and cosmetic formulations.